PEMBEKALAN GURU SEKOLAH MINGGU DI GMI BAITHANI PLAJU, PALEMBANG, SUMATERA SELATAN - Riky Handoko Sitindaon; Putri Rosinta Lestari (Jurnal PKM Setiadharma, 2022)
The development of children's knowledge in the Digital Age is accelerating. Children are now following the times so that they are not left behind. So, in children's ministry, especially in the Church, it is necessary to hold a briefing for Sunday School teachers, where teachers who teach Sunday School children are equipped with more practical ministry knowledge. If teachers update themselves, it will be easier for them to reach today's children. The Sunday School children in GMI Baithani Plaju are very active, so the teachers must be creative. Therefore, it is hoped that through this community service in the form of seminars with training accompanied by discussions of teachers and teams, Sunday School teachers will be equipped to optimize their creativity in service so that in Sunday School services, there are new things to show and make children enthusiastic in worshipping in Sunday School. This community service uses the method of seminars and discussions as well as practice to provide understanding to GMI Baithani Sunday School teachers to teach creatively and develop their creativity to foster the enthusiasm of Sunday School children in worship and ultimately strengthen children's faith.